Phage therapy for treatment of virulent Klebsiella pneumoniae infection in a mouse model. (June 2020) - Anand, Taruna; Virmani, Nitin; Kumar, Sudarshan; Mohanty, Ashok Kumar; Pavulraj, S.; Bera, Bidhan Ch.; Vaid, Rajesh K.; Ahlawat, Umang; Tripathi, B.N.
Highlights: Klebsiella pneumoniae is an emerging pathogen of humans and animals. A thermotolerant lytic bacteriophage was isolated and characterised in vitro as a phage therapy candidate. Protein constituents of the lytic phage were analysed by SDS-PAGE and nLC-MS/MS. Therapeutic efficacy was observed at 2 h post-challenge with virulent K. pneumoniae in a BALB/c mouse model. Abstract: Objectives: Klebsiella pneumoniae is an important emerging pathogen of humans and animals leading to serious clinical consequences. Increased antibiotic use has promoted the emergence of carbapenem-resistant and extended-spectrum β-lactamase (ESBL)-producing K. pneumoniae strains. Recently, phage therapy has gained momentum as a possible alternative against emerging antimicrobial resistance. This study was performed to assess the therapeutic effects of a novel lytic phage (VTCCBPA43) in a pneumonic mouse model in order to explore the efficacy of phage therapy against virulent K. pneumoniae infection. Methods: The tailed phage VTCCBPA43 was assessed for its growth kinetics, in vitro host range, and temperature and pH sensitivity. Protein constituents were analysed by SDS-PAGE and nLC-MS/MS. Therapeutic efficacy was observed 2 h post-challenge with virulent K. pneumoniae in a BALB/c mouse model. Results: Phage VTCCBPA43 was found to be highly temperature-tolerant (up to 80 °C). It was most active at pH 5, had a burst size of 172 PFU/mL and exhibited a narrow host range. It was identified as a KP36-like phage by shotgun proteomics. Following intranasal application of a single dose (2 × 10 9 PFU/mouse) post-challenge with virulent K. pneumoniae, the presence of biologically active phage in vivo and a significant reduction in the lung bacterial load at all time points was observed. A reduction in lesion severity suggested overall beneficial effects of VTCCBPA43 phage therapy in the pneumonic mouse model. Conclusion: This research represents the first in vivo evidence of effective phage therapy against K. pneumoniae infection by the intranasal route.